Before, during and after crossing the border: narrating the 'visa-free Grodno'. Issue 2 (3rd April 2019) - Kudžmaitė, Gintarė
Abstract : On 26 October 2016, Belarus introduced a visa-free border crossing regime for travellers visiting the Augustow Canal area and the city of Grodno. Based on a multi-method study, this article aims at investigating how this 'visa-free regime' is enacted and 'narrated' before, during and after border crossing. First, it analyses the website 'grodnovisafree.by' and searches for patterns of what the visitors encounter before travelling to the border area. Second, it analyses the border crossing experience, based on a participant observation while crossing the border from Lithuania to Belarus. Third, it investigates the linguistic and multimodal landscape after crossing the border in the city of Grodno. This study concludes that the 'real' 'narrative' about challenges and boundaries that the visitors have to overcome to cross the border is at times overshadowed by the 'ideal' picture of easily accessible Grodno and its area.